2020
DOI: 10.21203/rs.2.12866/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Skin transcriptome reveals the periodic changes in genes underlying cashmere (ground hair) follicle transition in Cashmere goats

Abstract: Background: Cashmere goats make an outstanding contribution to the livestock textile industry and their cashmere is famous for its slenderness and softness and has been extensively studied. However, there are few reports on the molecular regulatory mechanisms of the secondary hair follicle growth cycle in cashmere goats. In order to explore the regular transition through the follicle cycle and the role of key genes in this cycle, we used a transcriptome sequencing technique to sequence the skin of Inner Mongol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Among these genes, LHX2 functions as a transcriptional activator in hair follicle stem cells and is an essential positive regulator of hair formation (RheePolak and Fuchs 2006;Tornqvist et al 2010). Furthermore, the expression of LHX2 was upregulated during hair follicle differentiation, and the expression abundance was constant throughout the development cycle in secondary hair follicles of cashmere goats (Wu et al 2020;Yang et al 2020). In contrast, DENND1A and CRB2, which function in endocytic trafficking to mediate the recycling of selective cargos and early embryonic development, respectively (Xiao et al 2011;Shi et al 2019), were expressed lowly in the fetal stage of goat skin and showed very low expression during the cycle of adult cashmere fiber growth (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these genes, LHX2 functions as a transcriptional activator in hair follicle stem cells and is an essential positive regulator of hair formation (RheePolak and Fuchs 2006;Tornqvist et al 2010). Furthermore, the expression of LHX2 was upregulated during hair follicle differentiation, and the expression abundance was constant throughout the development cycle in secondary hair follicles of cashmere goats (Wu et al 2020;Yang et al 2020). In contrast, DENND1A and CRB2, which function in endocytic trafficking to mediate the recycling of selective cargos and early embryonic development, respectively (Xiao et al 2011;Shi et al 2019), were expressed lowly in the fetal stage of goat skin and showed very low expression during the cycle of adult cashmere fiber growth (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…18 and 19). It is known that cashmere fiber growth has three different periods in one year: a growth period (March-September), a regression period (September-December), and a resting period (December-March) (Yang et al 2020). Therefore, the deletion of the LHX2 insulator increases the expression of LHX2 and promotes cashmere fiber growth at the anagen stage, while deletion of the FGF5 enhancer reduces the expression of FGF5, inhibiting the regression.…”
Section: Biological Function Of the 582 Bp Deletionmentioning
confidence: 99%
“…Under the periodic changes of the natural photoperiod, the growth of cashmere in the Inner Mongolian cashmere goat presents a seasonal pattern. Normally, a typical hair follicle growth cycle starts in July and stops in March of the following year with shedding of the cashmere at April [5].…”
Section: Introductionmentioning
confidence: 99%
“…The hair follicle growth cycle of the cashmere goat can be divided into three phases: anagen, catagen and telogen, which are regulated by specific genetic regulators [5]. For Inner Mongolian cashmere goats, the anagen phase of SHFs is from April to November, the catagen phase is from December to January, and the telogen phase is from February to March [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation